2017
DOI: 10.1007/s12038-017-9695-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the hepatitis C virus core and its association with development of hepatocellular carcinoma

Abstract: Little is known about the mechanisms underlying hepatocellular carcinoma (HCC). Some studies have focused on the role of HCV viral proteins in hepatocyte transformation. In this work we have compiled and analysed current articles regarding the impact of polymorphisms in the HCV core gene and protein on the development of HCC. An exhaustive search for fulltext articles until November 2016 in PubMed database was performed using the MeSH keywords: 'hepatitis C', 'polymorphisms', 'core', 'hepatocellular cancer' an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…For example, it has been shown that HCV genotype 3 is associated with higher risk of developing HCC (36) and with lower rates of treatment success for direct-acting antivirals (7,8). Furthermore, amino acid variation in the NS5A protein is associated with viral load (9,10) and amino acid variation in the core protein is associated with the development of HCC (11).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that HCV genotype 3 is associated with higher risk of developing HCC (36) and with lower rates of treatment success for direct-acting antivirals (7,8). Furthermore, amino acid variation in the NS5A protein is associated with viral load (9,10) and amino acid variation in the core protein is associated with the development of HCC (11).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that HCV genotype 3 is associated with a higher risk of developing HCC ( Nkontchou et al, 2011 ; Kanwal et al, 2014 ; El-Serag et al, 2016 ; Lee et al, 2019 ) and with higher rates of direct-acting antiviral treatment failures ( Jacobson et al, 2013 ; Lawitz et al, 2013 ). Furthermore, amino acid variation in the NS5A protein is associated with viral load ( Ansari et al, 2017 , 2019 ), and amino acid variation in the core protein is associated with the development of HCC ( Sedeño-Monge et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…IL7RA rs987106 showed a weaker association with the progression of liver disease while IL7RA rs3194051 did not [20]. Therefore, although current DAAs have been a transcendental change in treatment of HCV liver diseases, modifying substantially their natural history; genetic polymorphisms can be a very important tool in the management of HCV liver disease [21] and will be probably a key factor in the evolution of patients once the sustained viral response with antiviral treatment has been achieved.…”
mentioning
confidence: 99%